2018
DOI: 10.1016/j.celrep.2018.04.107
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor Activation Underlies the Loss of Spinal Dorsal Horn Neurons and the Transition to Persistent Pain after Peripheral Nerve Injury

Abstract: Peripheral nerve lesions provoke apoptosis in the dorsal horn of the spinal cord. The cause of cell death, the involvement of neurons, and the relevance for the processing of somatosensory information are controversial. Here, we demonstrate in a mouse model of sciatic nerve injury that glutamate-induced neurodegeneration and loss of γ-aminobutyric acid (GABA)ergic interneurons in the superficial dorsal horn promote the transition from acute to chronic neuropathic pain. Conditional deletion of Grin1, the essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 55 publications
1
69
1
Order By: Relevance
“…1). PKC␥ interneurons lose inhibitory connections after neuropathic injury (Lu et al, 2013;Petitjean et al, 2015), and this loss might result from apoptosis of inhibitory interneurons or simply a loss of inhibitory contacts onto the PKC␥ soma (Petitjean et al, 2015;Inquimbert et al, 2018). The results of Alba-Delgado et al (2018) suggest that 5-HT 2A R-mediated morphological reorganization reduces the dendritic arbor of PKC␥ interneurons during inflammation.…”
Section: Review Of Alba-delgado Et Almentioning
confidence: 99%
“…1). PKC␥ interneurons lose inhibitory connections after neuropathic injury (Lu et al, 2013;Petitjean et al, 2015), and this loss might result from apoptosis of inhibitory interneurons or simply a loss of inhibitory contacts onto the PKC␥ soma (Petitjean et al, 2015;Inquimbert et al, 2018). The results of Alba-Delgado et al (2018) suggest that 5-HT 2A R-mediated morphological reorganization reduces the dendritic arbor of PKC␥ interneurons during inflammation.…”
Section: Review Of Alba-delgado Et Almentioning
confidence: 99%
“…Local modifications within the SC-DH have been shown to underlie the development of this chronic condition. The most prominent example is persistent local disinhibition, in the form of the robust pruning of inhibitory synapses from parvalbumin (PV) interneurons onto PKCγ excitatory interneurons [26] or the excitotoxic cell death of γ-aminobutyric acid (GABAergic) inhibitory interneurons [27]. Modifications in descending supraspinal inputs are also engaged.…”
Section: The Acute To Chronic Transition Of Tactile Allodynia After Nmentioning
confidence: 99%
“…the rat but also in mice, some groups have observed a decrease in the numbers of spinal neurons (Inquimbert et al, 2018). The mechanism for this is hypothesized to be primarily excitotoxic, and some groups have described a rescue of these phenotypes with both caspase inhibition or anti-oxidant treatments (Scholz et al, 2005;Yowtak et al, 2013) However, these hypotheses remain controversial.…”
Section: Anatomical Loss Of Gabaergic Neuronsmentioning
confidence: 99%
“…Multiple detailed stereological anatomical studies have suggested there is no loss of GABAergic neurons following nerve injuries, and two independent groups have suggested tactile allodynia occurs in the absence of a decrease in GABAergic neurons (Polgár et al, 2003(Polgár et al, , 2005Polgár and Todd, 2008;Leitner et al, 2013). Moreover, the estimates from the groups who report dorsal horn cell death vary very widely, from as little as 10% in lamina I-II of the dorsal horn to as much as 25% of total neurons in the dorsal horn (Scholz et al, 2005;Inquimbert et al, 2018). Finally, the dying cells have not been reliably identified as neurons and other groups suggest that the apoptotic profiles are co-localized with microglial markers (Polgár et al, 2005).…”
Section: Anatomical Loss Of Gabaergic Neuronsmentioning
confidence: 99%